2023
DOI: 10.1177/00220027221148655
|View full text |Cite
|
Sign up to set email alerts
|

Local Ceasefires and De-escalation: Evidence From the Syrian Civil War

Abstract: Local ceasefire agreements are prevalent in modern civil wars, but we know little about their impact. This study analyzes geo-referenced data on 145 local ceasefire agreements declared during the Syrian Civil War, 2011-2019, exploring their short- and long-term effects on the intensity of armed violence. Drawing on scholarship on gradual confidence-building processes, we theorize the conditions under which local ceasefire agreements may generate trust and reduce conflict intensity. Using interrupted time-serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Karakus and Svensson 2020; Sosnowski 2020) which suspend hostilities within a section of the larger battlefield These local arrangements are a common but poorly understood part of conflict (also see Duursma (2022)). Lundgren, Svensson, and Karakus (2022) , in this special section, show that the contents of a ceasefire also matter for local ceasefire. They find that violence is more likely to decrease in cases where agreements include provisions for stepwise implementation, that is, they detail how an agreement will be rolled out in a gradual manner.…”
Section: What Makes Ceasefires Last?mentioning
confidence: 81%
See 3 more Smart Citations
“…Karakus and Svensson 2020; Sosnowski 2020) which suspend hostilities within a section of the larger battlefield These local arrangements are a common but poorly understood part of conflict (also see Duursma (2022)). Lundgren, Svensson, and Karakus (2022) , in this special section, show that the contents of a ceasefire also matter for local ceasefire. They find that violence is more likely to decrease in cases where agreements include provisions for stepwise implementation, that is, they detail how an agreement will be rolled out in a gradual manner.…”
Section: What Makes Ceasefires Last?mentioning
confidence: 81%
“…For practitioners, we note in particular that contexts favorable to ceasefires are shown to be those with a recent history of collaboration between the conflict parties (Lundgren, Svensson, and Karakus (2022)), and other state-non-state dyads (Bara and Clayton (2022)). Successful ceasefires are also shown to create an environment more favorable for political settlements by providing cover for rebels.…”
Section: Implications For Research and Practicementioning
confidence: 98%
See 2 more Smart Citations
“…States can use ceasefire to build a reputation for cooperation. Prior ceasefire research has revealed the important signaling role that ceasefires can perform during a peace process, but has until now focused only on the direct relationship between a state and non-state group (Clayton and Sticher 2021), or between non-state groups (Duursma 2022; Lundgren, Svensson, and Karakus 2022). We extend this work, showing the broader role that ceasefires play in shaping the reputation of a state, and how this impacts other concurrent peace processes.…”
Section: Introductionmentioning
confidence: 99%